2020
DOI: 10.1055/s-0039-1701017
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and Fibrinogen: Emerging Complexity in Trauma-Induced Coagulopathy

Abstract: Trauma induces a change in nearly every observable aspect of hemostasis, generally tipping the balance toward trauma-induced coagulopathy (TIC) and bleeding in the critical early stages. Two particularly important aspects of TIC are platelets and fibrinogen, which are the primary determinants of clot formation and hemostasis. Their loss and dysfunction represent important transition points between coagulopathy phenotypes, highlighting their mechanistic roles in TIC as well as unveiling new potential avenues to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 120 publications
(136 reference statements)
1
4
0
Order By: Relevance
“…However, we also found reduced platelet counts in nonsurviving patients from day 0 to 10 after injury as compared with those in surviving patients but these differences were not stated as signi cant. These ndings are in line with previously published studies that reported increased mortality in patients with reduced platelet counts at admission [44][45][46][47] .…”
Section: Discussionsupporting
confidence: 93%
“…However, we also found reduced platelet counts in nonsurviving patients from day 0 to 10 after injury as compared with those in surviving patients but these differences were not stated as signi cant. These ndings are in line with previously published studies that reported increased mortality in patients with reduced platelet counts at admission [44][45][46][47] .…”
Section: Discussionsupporting
confidence: 93%
“…Studies have found impairment of different and sometimes conflicting agonist pathways, though the degranulation mechanism appears to remain intact 12 . The platelet dysfunction phenotype may be induced by ligand alteration, surface receptor inhibition, receptor shedding, and/or cellular metabolic dysfunction 8,13 . While much of the research in this area focuses on the platelet behaviors, a great deal can also be learned from the plasma environment after injury, which may directly alter platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…24 In addition, increased proteolysis after trauma can degrade both fibrinogen and fibrin, reducing their function and creating products of degradation that can alter hemostasis. 25…”
Section: Fibrinogenmentioning
confidence: 99%
“…There are many proposed causes for decreased fibrinogen following major trauma, including blood loss, dilution, consumption, hyperfibrinolysis, hypothermia, and acidosis 24 . In addition, increased proteolysis after trauma can degrade both fibrinogen and fibrin, reducing their function and creating products of degradation that can alter hemostasis 25 …”
Section: Mechanismsmentioning
confidence: 99%